Kajian Pengelolaan Sarana dan Prasarana Pendidikan di Taman Kanak-Kanak Putra Udyana Denpasar - I Gusti Ayu Ketut Mertaningsih; Faustina Mawo; Sonia Wikantari; Basilius Redan werang (Al-Kindi, 2025)
This study aims to describe the actual condition of facilities and infrastructure (sarpras) at Putra Udyana Kindergarten, Denpasar, analyze the gap between the actual condition and the standard theory of early childhood education (PAUD) infrastructure management, and formulate strategic managerial solutions to improve its quality. The research method uses a qualitative approach with a case study design. Data were collected through observation, Dapodik document review, and interviews with the school. The results of the study indicate that Putra Udyana Kindergarten's infrastructure is quantitatively sufficient, but not yet optimal functionally in supporting center-based learning and Multiple Intelligences theory. There are three main problems: (1) the use of classrooms that are not in accordance with the principles of a stimulative learning environment, (2) the use of outdoor spaces that are not optimal as an exploratory learning area, and (3) infrastructure management that is not yet systemic and oriented towards learning quality. Managerial solutions are formulated in three stages, namely rearranging classrooms (short term), preparing a Master Plan for Infrastructure Development (medium term), and developing an Outdoor Learning Master Plan (long term). This research confirms that PAUD infrastructure management must shift from an administrative paradigm to a pedagogical paradigm based on the stimulating function of child development. Keywords: infrastructure and facilities management, PAUD, learning environment, Putra Udyana Kindergarten, Multiple Intelligences